Deleterious assembly of the lamin A/C mutant p.S143P causes ER stress in familial dilated cardiomyopathy - West, Gun; Gullmets, Josef; Virtanen, Laura; Li, Song-Ping; Keinanen, Anni; Shimi, Takeshi; Mauermann, Monika; Helio, Tiina; Kaartinen, Maija; Ollila, Laura; Kuusisto, Johanna; Eriksson, John E.; et al. (Journal of Cell Science, 2016)
Mutation of the LMNA gene, encoding nuclear lamin A and lamin C (hereafter lamin A/C), is a common cause of familial dilated cardiomyopathy (DCM). Among Finnish DCM patients, the founder mutation c.427T>C (p.S143P) is the most frequently reported genetic variant. Here, we show that p.S143P lamin A/C is more nucleoplasmic and soluble than wild-type lamin A/C and accumulates into large intranuclear aggregates in a fraction of cultured patient fibroblasts as well as in cells ectopically expressing either FLAG- or GFP-tagged p.S143P lamin A. In fluorescence loss in photobleaching (FLIP) experiments, non-aggregated EGFP-tagged p.S143P lamin A was significantly more dynamic. In in vitro association studies, p.S143P lamin A failed to form appropriate filament structures but instead assembled into disorganized aggregates similar to those observed in patient cell nuclei. A whole-genome expression analysis revealed an elevated unfolded protein response (UPR) in cells expressing p.S143P lamin A/C. Additional endoplasmic reticulum (ER) stress induced by tunicamycin reduced the viability of cells expressing mutant lamin further. In summary, p.S143P lamin A/C affects normal lamina structure and influences the cellular stress response, homeostasis and viability.
EVALuna2:7332